Effectiveness of Emotion Regulation Program on Depression in Community - Chondaeng, Kongkrissadakorn; Luprasong, Somchit; Srisuwan, Kantarin; Saithanu, Kesorn; Thanee, Sanguan (Journal of health and health management, 2023)
This study was Quasi-Experimental Research. The objective of the study was to examine the effectiveness of the Emotion Regulation Program with depression in a community in Ubon Ratchathani Province. The sample consisted of 40 people with depression in the community who were assessed with 9 Questions rating scale questionnaire: 9 Q and had a score of 7 up with qualifications according to the inclusion criteria. The samples were divided into two groups; the experimental group and the control group. There were 20 people in each group by using the simple random sampling method. The experimental group was given the Emotion Regulation Program with depression in the community. There were 5 activities. The control group received regular nursing care. The instruments used were; 1) The personal data questionnaire 2) 9 Questions rating scale questionnaire: 9 Q which had a questionnaire reliability of .95. 3) The Emotion Regulation Program with depression in the community which had a questionnaire reliability of .82. The data were analyzed using descriptive statistics and t-test statistics. The results of the study were as follows: 1) The mean scores of depression assessments after receiving the Emotion Regulation Program were significantly lower than before the trial at the .01 level (t=8.47). 2) The mean scores for the depression assessments of the Emotion Regulation Program were statistically significant lower than those in the normal nursing group at .01 (t=-4.97). Therefore, from the results of the study, it can be concluded that the Emotion Regulation Program with depression in a community is an effective program for reducing depression among people with depression in the community.